Проблеми наукової школи в харківській славістиці середини ХІХ ст.: О. О. Потебня і П. О. Лавровський - Шевченко, Л.І.; Дядищева-Росовецька, Ю.Б. (Мовознавство, 2018)
У статті розглянуто проблеми непростого спілкування двох яскравих представників інтелектуального кола в харківській славістиці середини ХІХ ст. — Олександра Опанасовича Потебні та Петра Олексійовича Лавровського, «учня й учителя».
Виявлено парадоксальну ситуацію, коли функції «вчителя» змушений був виконувати талант, а «учня» — геній. The article explores the concept of «scientific school» in its historical, traditional sense
and modern interpretation.The analysis of the formation, development and complex ways
of formation of Kharkiv historical-philological school in the nineteenth century is offered.
The role of P. O. Lavrovsky in the formation of О. O. Potebnia as a researcher-humanitarian
is emphasized: it was his support for the preparation of O. O. Potebnia for the examination
of the master’s degree in Slavic literature, the assignment to the university, the formation of
a comparative worldview and the further reception of ideas in the world of scientific Slavic
studies, primarily linguistics and folklore.